Pengaruh Penerapan Metode Scramble dalam Pembelajaran Nahwu terhadap Pemahaman Siswa - Trismawati, Irma; Nurhamim, Nurhamim; Ubaidillah, Ubaidillah (AS-SABIQUN, 2025)
The purpose of this study was to examine how the use of the Scramble technique affects students' understanding of Nahwu. An experiment with a quantitative design was the methodology used in this study. A total of 56 students were sampled, divided into two groups: the experimental group, which used the Scramble approach, and the control group, which used the traditional method. A written test with questions regarding Nahwu content and observations was used as a data collection tool. The results of the pre-test and post-test were collected, and a t-test was used to analyze the data and determine whether the pre-test and post-test results of the two groups were different. The findings showed that students' understanding of Nahwu content increased significantly after the application of the method.